Niche overlap of two sympatric‐nesting hawks Accipiter spp. in the New Jersey‐New York Highlands - Bosakowski, Thomas; Smith, Dwight G; Speiser, Robert (Ecography, 1992)
The food and habitat niches of two nesting species of hawks Accipiter spp were studied in an extensively forested area of the Eastern Deciduous Forest Biome Nesting habitat was quantitated at 19 Cooper s hawk A cooperu nests and 16 northern goshawk A gentilis nests There was no significant trend for Cooper's hawks to nest in less mature forests than northern goshawks as reported previously for western North America Forest habitats did not differ markedly except that shrub cover was greater at Cooper's hawk nest sites, which were also on flatter terrain and closer to roads, forest openings, and human habitation However, these few differences resulted m reducing habitat‐niche overlap considerably (0 538), as was calculated using principal components analysis Mean prey weight was significantly larger for the northern goshawk which follows its 2 2‐fold body weight advantage over Cooper's hawk Although bird prey was of primary importance to both Accipiter, goshawks took twice the proportion of mammals compared to their smaller congener Food‐niche overlap was lowest by prey species overlap (0 470), followed by prey size class overlap (0 529), and highest by vertical foraging zone overlap (0 816) The Cooper's hawk showed the greatest niche breadth for both food and habitat niches indicating it as more of a generalist Overall, niche complementarity of food and habitat dimensions resulted in niche overdispersion along food and habitat dimensions with a total niche overlap (0 504) that was below the competition threshold These results suggested that competition (past and current) was responsible for segregating niches Copyright © 1992, Wiley Blackwell. All rights reserved
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/084-156-083-755-941 tex.type: [object Object]
Keywords: Accipiter cooperii; Accipiter gentilis; Cooper's hawk; USA; New Jersey; USA; New York; dept.bio; goshawk; hawk; niche overlap; northern goshawk